Comparison of Cavum Septum Pellucidum Size in Euploid and Aneuploid Fetuses - Merve Ozturk Agaoglu; Zahid Agaoglu; Filiz Halici Ozturk; Sevki Celen; Turhan Caglar (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2023)
Abstract Objective The aim of the present study is to compare the cavum septum pellucidi (CSP) z-score in euploid and aneuploid fetuses and to investigate the performance of the CSP width/length and CSP width/biparietal diameter (BPD) ratios as a diagnostic marker in aneuploidy. Methods A total of 54 patients, 20 aneuploid and 35 euploid fetuses, between 18 and 37 weeks of gestation, were included in this retrospective study. The CSP width z-score was compared between the two groups. Receiver operating characteristic (ROC) curves were calculated for the CSP width/length and CSP width/BPD ratios to predict aneuploidy. Results The median CSP width was 4.8 mm (range, 1.8 to 8.5 mm) in the euploid group, and 5.4 mm (range 3.1 to 8.4 mm) in the aneuploid group. Cavum septum pellucidi width z-score, CSP width/length ratio, and CSP width/BPD ratio were significantly higher in fetuses with aneuploidy than in fetuses with normal karyotype (p= 0.001; p= 0.013; p= 0.028). In the ROC analysis, the CSP width/length ratio had the optimal cutoff value of 0.59, with 72.0% sensitivity and 58.0% specificity, and for the CSP width/BPD ratio, the cutoff value was 0.081 with 83.0% sensitivity and 61.0% specificity for detection of aneuploidy. Conclusion CSP width z-score was found to be increased in aneuploid fetuses. The CSP width /BPD ratio can be used as a new marker for predicting aneuploidy.